Reflective approach to improve self-adaptation of Web service compositions with autonomic middleware. Issue 3 (27th September 2019) - Cherif, Sihem; Djemaa, Raoudha Ben; Amous, Ikram
Abstract : Purpose: This paper aims to propose an approach for the self-adaptation of the Web composition called SAMIWA. The SAMIWA framework helps users during the search, invocation and composition of the appropriate Web service. Design/methodology/approach: The authors' approach allows expressing requirements by taking into account potential users' context in addition to the functional one. Findings: In this paper, the authors introduce a new context-aware approach that provides a dynamic adaptation of service compositions. Originality/value: The author has implemented a Web application that enables selection and composition of the most appropriate composite service.